(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2025)
Background: The online commercial services have increased significantly over the last decade especially after the COVID-19 pandemic hit the world. Electronic commerce and mobile commerce have expanded significantly. Through these developments, it has become easier for people to access different kinds of information and develop interactions across the globe to conduct their business activities. The mobile commerce applications have made it efficient and economical to conduct shopping in Saudi Arabia as well. However, the managers of these companies are concerned about the loyalty of customers who use mobile commerce applications for making their purchases. Purpose: The purpose of this study is to investigate the impact of factors of customer satisfaction on customer loyalty for mobile commerce customers in Saudi Arabia. Mobile commerce applications have expanded significantly in Saudi Arabia especially after the COVID-19 pandemic. Many companies have established online presence to conduct businesses through mobile commerce platforms. This study has helped in identification of the antecedents of customer loyalty for mobile commerce customers in Saudi Arabia. Research Design and Methodology: The quantitative research methodology and cross-sectional research design have been used in this study. The questionnaire was developed and responses from the participants were achieved through sending the questionnaires via email. The sample size for this study was 100 participants. Findings: The dependent variable of the study was customer loyalty while independent variables include perceived ease of use, perceived use, customer satisfaction, trust, and continuance intention. According to the empirical analysis, perceived ease of use has no significant influence on customer loyalty. On the other hand, the analysis revealed that perceived use, customer satisfaction, trust, and continuance intention have a significant positive impact on customer loyalty. Furthermore, the findings suggest that the perceived use has the strongest impact on the customer loyalty while trust has very weak influence on customer loyalty for mobile commerce customers in Saudi Arabia. Practical Implications: The findings of this study have important policy and strategic implications for the mobile commerce companies in Saudi Arabia. For the managers who are concerned about the customer loyalty for mobile commerce customers, the findings of this study have provided the antecedents that have impact on customer loyalty. These managers can develop their policies and strategies through which they can develop a sense of loyalty in their customers. Customer loyalty is considered as a very important asset because the company does not have to incur huge costs in acquiring new customers when it has a strong base of loyal customers. Originality/Value: The theoretical model of this study is very unique and this kind of study has never been performed in Saudi Arabia. This is the kind of study which is needed after immediate adoption of mobile commerce channel by a lot of companies during COVID-19 pandemic. This study has successfully highlighted the factors that can lead to customer loyalty of mobile commerce customers in Saudi Arabia. Limitations and Future Research Directions: First, this study relies on collection of data from only one particular source which might not be reliable for developing comprehensive results and explanations. The time and resources for conducting this study were very limited due to which sample size comprised of just 100 participants. To achieve more representative sample and more generalizable findings, the sample size should have been larger. The future researchers should keep these limitations and recommendations in mind.